The Potential of Birds as Objects for Avitourism Interpretation in the Mandalika Special Economic Zone - Ade Rizky Ananda; Yeni Aryati Mulyani; Eva Rachmawati (Postgraduate, University of Mataram, 2025)
Birds provide various environmental benefits, including serving as tourist attractions in certain areas. Concerns over environmentally unfriendly tourist behaviors threaten bird communities, necessitating educational activities. Avitourism interpretation is an eco-friendly tourism approach that educates visitors on the importance of bird conservation in nature. This study aims to identify bird species and their distribution that have the potential to serve as interpretation objects for avitourism in the Mandalika Special Economic Zone. This study used the Mackinnon Species List method for bird data collection and literature review to determine potential objects for avitourism interpretation. Data analysis was conducted using descriptive-quantitative analysis. Based on the findings, 37 bird species were identified as having potential for interpretation as objects. These include bird species with high conservation status, endemic birds, birds with unique morphological characteristics, migratory birds, birds associated with cultural significance, and birds with the highest encounter frequencies. 65% of bird species identified as interpretation objects are distributed along the Novotel Mangrove trail. Based on avitourist preferences, the recommended trail for interpretation is the Novotel Mangrove trail for all categories of avitourists, particularly beginners with a preference for birds with unique morphological features and high encounter frequencies. Meanwhile, for intermediate and advanced avitourist categories, the Gerupuk Mangrove, Songgong Mangrove, Merese Plantation, and Merese Hill trails are also recommended because they feature endemic bird species, species with high conservation status, and migratory birds that can only be found in those trails.